Simulating self-similar vbr traffic / Malini Subramaniam - Malini, Subramaniam (2004)
Studies on the nature of VBR traffic have shown that VBR traffic has self-similar characteristics. However, most traditional network traffic models that are used in the simulation of VBR traffic are unable to capture these self-similar qualities. As VBR traffic is forecasted to be a substantial portion of network traffic, it is imperative that the self-similarity of VBR traffic be taken into account whilst designing both network simulators and real networks. The aim of this project is to implement a module that will simulate self-similar VBR traffic. The module will be implemented in an existing network simulator: the UMJaNetSim network simulator. Users of the simulator will then be able to generate self-similar VBR traffic.